Bambini “dimenticati” e abbandoni “intenzionali” - Penta, Francesca (Il sogno della farfalla, 2019)
The aim of this article is to propose a reflection on the different modalities a child can be “forgotten”. The author, whose clinical activity is based on the Human Birth Theory, affirms that this occurs every time children are annulled in their mental and physical reality. Whether leaving a child in the car is an intentional or unaware act, this event still implies a violent pulsion addressed towards the child. Firstly, the main differences and analogies between intentional and unaware abandonment are outlined, considering if these two differ because of a different severity of the annulment pulsion. Secondly, data on children abuse discussed by the clinical literature are reported to question the causes leading a parent to this violent behaviour. Finally the author proposes some reflections on the possible consequences of repeated acts of violence on child’s thought and inner dimension.